THE GEOECOLOGICAL GIS BASED PLANNING ANALYSIS OF SULEYMANPASA (TEKIRDAG) - Halid PEKTEZEL (Fırat University, 2019)
Today, accelerating settlements are causing many problems in natural environment. To build living spaces which are compatible with natural environment elements, healthy and ecological, the studies on suitable places and field planning are needed. With regards to this need, remarkable studies are being carried on depending on the techniques of Geographical Information Systems (GIS). This study is a GIS based geoecological planning analysis to determine inhabitable places in Süleymanpaşa - the central district of Tekirdağ - in terms of natural and humane environmental elements. In the study, several thematic maps are used based on 1/25.000 scale. The analysis and mapping stage are completed by using ArcGIS/ArcMap 10.2 programme, as one of the GIS software. The poly-criterion analysis process is applied as a method. 16 effective factors in the analysis are explained, classified, and GIS degrees are given. Afterwards, these factors are used to determine the inhabitability of the field and the compatibility map of the field is prepared in terms of the inhabitability. As a result of our studies, it is observed that 26,5% of Süleymanpaşa consists of uninhabitable areas, 42,8% consists of habitable and 30,6% is semi-habitable. The uninhabitable areas are river beds and their surroundings, sloping and mountainous lands near the Ganos fault and the lands that are far away from the sea, the port and public service areas. The habitable areas are those that do not have slope or foundation problems, close to the transportation systems and public service areas. It is observed that the inhabitable lands lay through Tekirdağ - Çorlu - İstanbul highway and Tekirdağ - Muratlı railway course. At the same time, these lands have lower slope angles and their average altitude is below 100 meters. The fact that these lands are without a drainage problem and face the sea in the south makes them more suitable for habitation. It is found out in this study that Gazioğlu, Hüsünlü, Karaselvi, Köseilyas, Klavuzlu, Kayı, Gündoğdu, Karadeniz, Zafer, Eski Cami-Orta Cami, Çanakçı, Hacıköy, Yazır, Yağcı and Nusratlı neighborhoods are habitable. Whereas, Dedecik, Kınıklar, Akçahalil, Oruçbeyli, İnecik, Karansallı, Karacamurat and Evciler neighborhoods are inhabitable. Safety precautions against natural disasters must be taken for the neighborhoods on the inhabitable lands. It is thought that such precautions and studies should be taken into consideration for the lands that are zoned for hou